Karakteristik dan Profil Pasta Pati Sagu Modifikasi Pragelatinisasi pada Suhu yang Berbeda - Fitriani, Shanti; Yusmarini, Yusmarini; Riftyan, Emma; Saputra, Edo; Rohmah, Mega Chafiatun (Universitas Sebelas Maret (UNS), 2023)
Pregelatinized starch is a common type of physically modified starch with wide applications, especially in the food industry. This study aimed to obtain information about the effect of cooking temperature on the characteristics of pregelatinized sago starch and to obtain the best cooking temperature. The treatment in this study was variation in cooking temperature without pregelatinization (control), 50°C, 60°C, 70°C, 80°C, 90°C, and 100°C. Data obtained were statistically analyzed using Analysis of Variance (ANOVA) and continued with Duncan’s Multiple Range Test (DMRT) at a 5% level. The results showed that variations in pregelatinization temperature significantly affected all observed parameters. The best treatment was pregelatinization temperature 90°C, with moisture, amylose content, swelling power, starch solubility, WHC, and gelatinization degree of 13%; 24,94%; 16,90 g/g; 58,22%; 131,06%; and 42,17% respectively. The gelatinization profile of sago starch was selected with the respective viscosity values: peak 5473 cP, heat 1509 cP, breakdown 3964 cP, final 2964 cP, and setback 1419 cP.